Relationship between drug holiday of the antiresorptive agents and surgical outcome of medication-related osteonecrosis of the jaw in osteoporosis patients - Kota Morishita; Sakiko Soutome; Mitsunobu Otsuru; Saki Hayashida; Maho Murata; Miho Sasaki; Yukinori Takagi; Misa Sumi; Masahiro Umeda (Scientific Reports, 2022)
Abstract A drug holiday of 3 months does not promote separation of sequestra and is not correlated with treatment outcomes after surgical therapy in osteoporosis patients who receive antiresorptive agents and who have medication-related osteonecrosis of the jaw. Medication-related osteonecrosis of the jaw (MRONJ) is a serious adverse effect of antiresorptive agents alone or in combination with immune modulators or antiangiogenic medications, in the absence of radiation exposure to the head and neck region. The effectiveness of surgical treatment for MRONJ has been reported, but the timing of the operation remains controversial. The purpose of this study was to clarify whether preoperative drug holidays of antiresorptive agents promote sequestrum separation and improve treatment outcomes in patients who receive low doses of antiresorptive agents. This retrospective study included 173 patients who received low-dose antiresorptive agents and underwent surgical therapy. The effects of a drug holiday on the separation of sequestra and treatment outcomes were analyzed using logistic and Cox regression analyses. Multivariate analysis revealed that administration of an antiresorptive agent for more than 4 years, a high number of lymphocytes, and an extensive osteolytic area were significantly correlated with separation of sequestra, but drug holiday did not promote sequestrum separation. Furthermore, a drug holiday of 90, 120 or 180 days did not show any improvement in treatment outcomes. The drug holiday of the antiresorptive agents for the treatment of MRONJ is unnecessary, and surgical therapy should be performed early.